THU0031 ABATACEPT ALTERS THE FREQUENCY OF IMMUNOREGULATORY AND EFFECTOR T CELL SUBPOPULATIONS IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Dreo, B.; Prietl, B.; Kofler, S.; Sourij, H.; Lackner, A.; Moazedi-Fürst, F.; D'orazio, M.; Stradner, M.; Graninger, W.; Brezinschek, H. P.
Abstract : Background: Under physiological conditions, T regulatory cells (Tregs) are responsible for the downregulation of the immune response. In autoimmune diseases, such as rheumatoid arthritis (RA), auto-inflammation is driven by an imbalance of activation and downregulation of immunological pathways. Thus, treatment plans for autoimmune diseases often involve the enhancement of immunoregulatory pathways by administering inhibitors of costimulation, i.e. CTLA-4-Ig (abatacept, ABA). ABA binds specifically to CD80 and CD86 on antigen presenting cells (APC). Consequently, T cell activation via the CD28 receptor is blocked. Previous studies have demonstrated surprising effects of abatacept on Tregs, specifically decreased frequency of these cells but enhancement in their function 1 . Whether these alterations can only be found in patients with ABA treatment, or whether they are also present in patients receiving other anti-inflammatory drugs is currently unknown. Objectives: The aim of our research was to delineate the impact of ABA on the different subsets of effector and regulatory T cells in RA and compare these findings with patients receiving tocilizumab (TCZ) or rituximab (RTX). Methods: Peripheral blood samples from 56 RA patients (median ± SE; age: 60.5 ± 1.3 years, female ratio: 0.7, disease duration: 17.9 ± 2.1 years; respectively) were drawn over a sampling period of 2 years. Freshly isolated PBMCs of RA patients were stained with fluorochrome-labelled antibodies and T cell subsets were identified by flow cytometric means. CD3 + CD4 + T cells were further classified using different T cell markers (CD25, CD127, CD39, CD95). All cytometric measurements were performed using a standardized BD LSR-Fortessa platform. RA patients were compared according to their treatment with ABA, TCZ or RTX. Results: Eighteen out of 56 RA patients (32%) received ABA, 25 patients (45%) received TCZ and 13 patients (23%) were under CD20+ cell depletion therapy with RTX. RA patients receiving ABA displayed a significant decrease in CD3 + CD4 + CD25 + CD127 dim Tregs (3.7% ± 0.4) compared to patients with TCZ (5.4% ± 0.4, p = 0.041) and patients under RTX treatment (7.52% ± 0.93, p = 0.026). CD39 + Tregs were significantly higher in RA patients treated with TCZ (49.5% + 3.2, p = 0.000) or RTX (50.5% ± 5.3, p = 0.026) compared to patients receiving ABA (24.5% ± 3.1). In addition, the frequency of CD95 + Tregs was significantly reduced in ABA patients compared to RTX patients (59.6% ± 3.1 vs.76.7% ± 3.6, p = 0.014; respectively). Interestingly, T cells displaying an effector T cell phenotype (CD3 + CD4 + CD25 +/- CD127 + ) were increased in ABA treated patients compared to RTX treated patients (59.6% ± 3.1 and 76.7% ± 3.6, p = 0.002). Since none of our patients were a non-responder or had high disease activity, we could not analyse whether these changes are associated with treatment outcome. Conclusion: Our data demonstrate that blockage of T cell stimulation via ABA leads to characteristic alterations in different regulatory and effector T cells not seen in patients treated with TCZ or RTX. Further studies must clarify whether the analysis of regulatory and effector T cell subpopulations before treatment initiation can be used as biomarker for treatment response. References: [1]Álvarez-Quiroga C, Abud-Mendoza C, Doníz-Padilla L, et al. CTLA-4-Ig therapy diminishes the frequency but enhances the function of treg cells in patients with rheumatoid arthritis. J Clin Immunol . 2011;31(4):588-595. doi: 10.1007/s10875-011-9527-5 Acknowledgments: Work done in "CBmed" was funded by the Austrian Federal Government within the COMET K1 Centre Program, Land Steiermark and Land Wien. Disclosure of Interests: None declared